Global perspective in tourism development: positioning Malaysia as a culinary destination - ‪Leong, Quee Ling; Karim, Shahrim (IGI Global, 2015)
Malaysia offers a rich potpourri of delicious cuisines from diverse ethnicity. However, not much attention given to promote Malaysian food and the food seems to be ignored in the tourism industry. Furthermore, the concept of utilizing Malaysian food as a marketing means is tenuous. In this chapter, the image dimensions of Malaysian food and the effect of food images on tourists' satisfaction are discussed. Additionally, the influence of socio-demographic factors on tourists' perceived image is deliberated. Univariate and multivariate statistics are used to describe the obtained findings. The results of the study will significantly fill in the gap in the literature about Malaysian food's image and the potential of Malaysia being promoted as a food destination. Additionally, the results would indisputably provide better insight to the tourism and hospitality industry on the perceptions of international tourists towards Malaysian food and Malaysia as a food tourism destination.